2015
DOI: 10.1007/s11356-015-5118-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lead on the growth, content of primary metabolites, and antioxidant response of green alga Acutodesmus obliquus (Chlorophyceae)

Abstract: Green unicellular alga Acutodesmus obliquus (Turpin) Hegewald et Hanagata (SAG strain no. 276-6) (Chlorophyceae) was used for determination of phytotoxicity of lead (Pb) at the range of concentrations 0.01-500 μM during 7 days of culture. The accumulation of Pb in algal cells was found to be increased in a concentration- and duration-dependent manner. The highest Pb uptake value was obtained in response to 500 μM Pb on the seventh day of cultivation. The decrease in the number and the size of cells and the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 54 publications
(92 reference statements)
5
31
0
Order By: Relevance
“…The growth inhibition increased with the increasing of exposure time. This result was consistent with other previous reports, in which the toxicity of lead [16], cadmium [17] and chlorine [18] to algae was related to the incubation time. After 96 h exposure, the inhibition rates relative to the control group of 7.2, 10.8, and 14.4 μM Th were 22.5%, 55.1%, and 67.8%, respectively.…”
Section: Resultssupporting
confidence: 94%
“…The growth inhibition increased with the increasing of exposure time. This result was consistent with other previous reports, in which the toxicity of lead [16], cadmium [17] and chlorine [18] to algae was related to the incubation time. After 96 h exposure, the inhibition rates relative to the control group of 7.2, 10.8, and 14.4 μM Th were 22.5%, 55.1%, and 67.8%, respectively.…”
Section: Resultssupporting
confidence: 94%
“…The growth inhibition increased with the increasing of exposure time. This result was consistent with other previous reports, in which the toxicity of lead [21], cadmium [22] and chlorine [23] to algae was related to the incubation time. After 96 h exposure, the inhibition rates relative to the control group of 7.2, 10.8, and 14.4 μM Th were 22.5, 55.1, and 67.8%, respectively.…”
Section: Chemical Species Of Th In the Mediasupporting
confidence: 94%
“…Hence, 1 μM EBL was chosen in this experiment. The response of Pb action on A. obliquus cultures was presented in Piotrowska-Niczyporuk et al (2015. Thus, Pb at the concentrations of 0.01 and 500 μM was used.…”
Section: Algal Cultivationmentioning
confidence: 99%
“…Moreover, previous studies confirmed the toxic effect of Pb ions on the unicellular green alga. Heavy metal application caused the inhibition of growth and development of A. obliquus, as well as initiation of oxidative stress (Piotrowska-Niczyporuk et al 2015). Therefore, the role of EBL in the adaptation of A. obliquus to Pb stress was the main aim of this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation